Automatic control simulation environment system (ACSES) designed as a virtual tool for control education - SAVAŞ, KENAN (ELSEVIER SCIENCE BV, 2010)
This paper shows steps and tools needed to develop and set up a virtual control laboratory for technical and engineering education. It is mainly based on laboratory exercises given at Technical Education Faculty of Marmara University in Istanbul. For this purpose the Automatic Control Simulation Environment System (ACSES) is developed. Students or other users can access this system all around the world through Internet. By doing this, license costs will decrease. Only thing you need is a browser software This system is used to simulate different laboratory tasks, such as modelling and controlling (related to On-Off, PID etc.). The MATLAB and MATLAB Web Server (MWS) is used for modelling and making virtual exercises accessible from the Internet and also Web MWS System is also used to decrease the cost and having virtual simulations web-based. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Automatic control laboratory; control education; MATLAB; MATLAB web server (MWS); web MWS system; virtual laboratory; virtual experiment